Towards automized chaos verification - Day, Sarah; Junge, Oliver; Mischaikow, Konstantin (Proceedings of Equadiff 2003, International Conference on Differential Equations)

Average case complexity of Voronoi diagrams of n sites from the unit cube - Bienkowski, Marcin; Damerow, Valentina; Meyer auf der Heide, Friedhelm; Sohler, Christian (Proceedings of the 21st European Workshop on Computational Geometry, Eindhoven, The Netherlands, March 9-11, 2005)

Abstracts Collection -- Algorithmic Aspects of Large and Complex Networks

Adaptive Filter-and-Sum Beamforming in Spatially Correlated Noise - Haeb-Umbach, Reinhold; Warsitz, Ernst (International Workshop on Acoustic Echo and Noise Control (IWAENC 2005))
In this paper we propose a novel adaptation algorithm for Filter-and-Sum beamforming in spatially correlated noise. Deterministic and stochastic gradient ascent algorithms are derived from a constrained optimization problem, which iteratively estimate the principal eigenvecto r of a generalized eigenvalue problem. The method does not require an explicit estimation of the speaker location. It is shown that the well-known Delay-and-Sum beamformer and the previously introduced Filter-and-Sum beamformer in spatially white noise are obtained as special cases. Further, bounds on the maximally achievable SNR gains are derived and it is shown that the proposed adaptation algorithm is able to approach these performance bounds.

A Unified Probabilistic Approach to Error Concealment for Distributed Speech Recognition - Ion, Valentin; Haeb-Umbach, Reinhold (Interspeech 2005)
The transmission errors in a wireless or packet oriented network may dramatically decrease the performance of a distributed speech recognition DSR) system. Error concealment has been shown to be an effective way to mantain an acceptable word error rate when dealing with error prone communication channels. In this paper we propose an extension of our previously introduced soft features approach for the case that the soft-output of the channel decoder is not available at the server side of the DSR system. We found a simple method to estimate bit reliability information which still gives good speech recognition results. It is shown that some other error concealment schemes turn out to be special cases of the method proposed here.

A Comparison of Soft-Feature Distributed Speech Recognition with Candidate Codecs for Speech Enabled Mobile Services - Ion, Valentin; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2005))
In this paper we present a comparison of the recently proposed Soft-Feature Distributed Speech Recognition (SFDSR) with the two evaluated candidate codecs for Speech Enabled Services over wireless networks: Adaptive Multirate Codec (AMR) and the ETSI Extended Advanced Front-End for Distributed Speech Recognition (XAFE). It is shown that SFDSR achieves the best recognition performance on a simulated GSM transmission, followed by XAFE and AMR.We also present some new results concerning SFDSR which demonstrate the versatility of the approach. Further, a simple method is introduced which considerably reduces the computational effort.
Keywords: adaptive codes; adaptive multirate codec; AMR; distributed speech recognition; ETSI; extended advanced front-end; recognition performance; SFDSR; simulated GSM transmission; soft-feature distributed speech recognition; speech codecs; speech coding; speech recognition; variable rate codes; XAFE

Acoustic filter-and-sum beamforming by adaptive principal component analysis - Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2005))
For human-machine interfaces in distant-talking environments multichannel signal processing is often employed to obtain an enhanced signal for subsequent processing. In this paper we propose a novel adaptation algorithm for a filter-and-sum beamformer to adjust the coefficients of FIR filters to changing acoustic room impulses, e.g. due to speaker movement. A deterministic and a stochastic gradient ascent algorithm are derived from a constrained optimization problem, which iteratively estimates the eigenvector corresponding to the largest eigenvalue of the cross power spectral density of the microphone signals. The method does not require an explicit estimation of the speaker location. The experimental results show fast adaptation and excellent robustness of the proposed algorithm.
Keywords: acoustic filter-and-sum beamforming; acoustic room impulses; acoustic signal processing; adaptive principal component analysis; adaptive signal processing; architectural acoustics; constrained optimization problem; cross power spectral density; deterministic algorithm; deterministic algorithms; distant-talking environments; eigenvalues and eigenfunctions; eigenvector; enhanced signal; filter-and-sum beamformer; FIR filter coefficients; FIR filter coefficients; FIR filters; gradient methods; human-machine interfaces; iterative estimation; iterative methods; largest eigenvalue; microphone signals; multichannel signal processing; optimisation; principal component analysis; spectral analysis; stochastic gradient ascent algorithm; stochastic processes

Bestimmung des Anteils ungelöster Gase in flüssigen Medien - Gulsch, Michael; Henning, Bernd
Impulsbasierte Ultraschallsensorsysteme zur Messung von Füllstand, Durchfluss und Konzentration sind heutzutage aufgrund ihrer Robustheit und Wartungsfreundlichkeit weit verbreitet. Probleme treten immer dann auf, wenn sich Gasblasen im Medium befinden. Diese verändern das empfangene Signal derart, dass eine exakte Messung der Schallgeschwindigkeit des flüssigen Mediums nicht mehr möglich ist. Dieser Beitrag behandelt eine neue Art der Signalauswertung, die eine zuverlässige Bestimmung der Schallgeschwindigkeit auch in diesem Fall gewährleistet. Darüber hinaus können auch Rückschlüsse auf den Gasanteil innerhalb des flüssigen Mediums gewonnen werden.

Bubble detection and gas volume measurement in bubble loaded liquids with pulse driven measurement devices - Gulsch, Michael; Henning, Bernd (2005 IEEE Ultrasonics Symposium)
Currently there are pulse based ultrasonic sensor systems used to measure flow, liquid level, concentration or in process monitoring. In several processes the investigated media are a mixture of liquid and solid ingredients (emulsions, suspensions). The use of ultrasonic sensor systems will be very complicated if gas bubbles appear at the measurement place caused by chemical reactions, high temperature or fast flow that means by typical process conditions. Firstly, the appearance of gas bubbles falsifies the measured absorption. Secondly, the measured velocity is influenced by gas bubbles. In figure 1 is visible that a volume fraction of 0.1 ppm of undissolved air decreases the sound velocity by 1.4 m s-1

Gasvolumenmessung in blasenbeladenen Flüssigkeiten - Gulsch, Michael; Henning, Bernd (Fortschritte der Akustik - DAGA '05)
In vielen verfahrenstechnischen Prozessen ist die kontinuierliche Regelung von Prozessgrößen für einen stabilen und sicheren Betrieb eine wichtige Vorraussetzung. Die Erfassung der Zielgrößen geschieht aufgrund von hoher Robustheit und Wartungsfreundlichkeit zunehmend mit akustischen Messverfahren. Besonders impulsbasierte Messsysteme werden häufig zur Messung von Durchfluss, Füllstand und in der Flüssigkeitsanalytik auch zur Konzentrationsmessung benutzt. Dabei führen am Messort auftretende Gasblasen zu großen messtechnischen Problemen. Sie verändern die gemessenen akustischen Stoffkenngrößen, wodurch es zur fehlerhaften Regelung bestimmter Prozesszielgrößen kommt.

Visualisation and Measurement of Condensed Water in Automobile Headlights - Gulsch, Michael; Unverzagt, Carsten; Henning, Bernd; Nolte, Sascha
Today headlights are built with transparent polycarbonate front windows. If the air moisture inside the headlight is high and the outside temperature decreases below the dew-point, the air moisture condensates inside and the inner surface of the polycarbonate front window (PCFW) becomes nontransparent (figure 1). To the costumer this appears as an optical defect.In order to avoid the condensation and to speed up the evaporation of the condensed water (condensate) on the PCFW a Computational-Fluid-Dynamic-simulation is used. The simulation results are proceeded to optimise the airflow and the arrangement of the breather holes. An important problem is the validation of the simulated results with the reality. It was necessary to build a non-invasive measurement system for the continuous characterisation of condensated areas without affecting the material properties, the airflow and the light distribution inside the headlight.

Quantum 1/f Effect in Resonant Biochemical Piezoelectric and MEMS Sensors - Handel, Peter; Tournier, Adam; Henning, Bernd (IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control)

Acoustic properties of highly attenuating isotropic media - Rautenberg, Jens; Henning, Bernd
In the 1950's many investigations have been made in measuring the Young's and the shear modus of isotropic materials with acoustic waves. Therefore both the longitudinal and transversal sound velocities have been determined with only one specimen, that had to be large in comparison to the wavelength (Brown, Reynolds, Dunegan). Therewith the method was suited only for low absorbing materials. In the 1990's further developments led to mono mode rods to describe viscoelastic properties. Their diameters had to be very small for high frequencies, thus giving practical values up to 65 kHz (Benatar). This contribution is about a tubular multi mode specimen and its application for the simultaneous measurement of the abovementioned acoustic properties at high frequencies.

Charakterisierung einzelner Ultraschallwandler für den Aufbau eines mehrelementigen parametrischen Lautsprechers - Rautenberg, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA '05)
In den bekannten grundlegenden Ausf¨uhrungen zur Erzeugung hörbaren Schalls durch Eigendemodulation amplitudenmodulierten Leistungsultraschalls (siehe u.a. Westervelt, Berktay) wird von zwei räumlich übereinander liegenden Wellen unterschiedlicher Frequenz im nichtlinearen Medium ausgegangen, so dass neben ihren Harmonischen auch Summen- und Differenzfrequenzen entstehen. Die perfekte räumliche Ueberdeckung der Wellen im Freifeld kann mit herkömmlichen Schallwandlern allerdings nur unzul¨anglich erreicht werden. Trotzdem sind in der Vergangenheit einige so genannte parametrische Lautsprecher entwickelt worden. Um annähernd die erwähnten Voraussetzungen zu gewährleisten, sind gängige Systeme mit einem Durchmesser von ca. 30 cm relativ groß. Dies soll auch dem angestrebten Sekundärschalldruck Rechnung tragen, der linear mit der effektiv abstrahlenden Fl¨ache wächst. Zum Aufbau dieser großen Flächen werden teilweise viele kleine Ultraschallwandler zu einem Array zusammengesetzt. Der hohe Preis einzelner Wandler aber auch die notwendige Sortierung beispielsweise bezüglich ihrer Mittenfrequenz macht den Aufbau solcher Systeme aufwändig. Erst am vollständig aufgebauten Array werden schließlich Frequenzgang und Richtcharakteristik des Sekundärschalls ermittelt. Im Sinne kürzerer Entwicklungszeiten und -kosten wäre es wünschenswert, bereits vor dem Aufbau des Arrays allein durch Untersuchung des einzelnen Ultraschallwandlers eine Prognose über die zu erwartenden Eigenschaften des Gesamtsystems vornehmen zu können. In diesem Beitrag wird ein Versuchsaufbau vorgestellt, der unter strenger Beachtung der anfangs erwähnten Voraussetzungen die parametrische Schallerzeugung mit nur einem Ultraschallwandler kleiner Baugröße erlaubt. Die Frequenzg änge des Sekundärschalls von Einzelelement und Array werden bei entsprechender Distanz gegen¨ubergestellt. Vorzüge des neuen Messaufbaus, beispielsweise die Möglichkeit zur Variation von Druck, Temperatur oder Luftfeuchtigkeit, um atmosphärische Einflüsse auf die parametrische Schallerzeugung zu untersuchen, werden skizziert

Lower Frequency Bound of Parametric Arrays - Rautenberg, Jens; Henning, Bernd
One method to generate focused sound is to transmit amplitude modulated ultrasound of high energy in a nonlinear medium, so that sum and difference frequencies develop. Practically wide arrays of many small ultrasonic transducers are used, but the generation of very low frequencies is always weak. This contribution is about the experimental investigation of the {\textquotedbl}generation zone{\textquotedbl} -- that is the distance between the ultrasonic loudspeaker and the listener -- and the decrease of the lower frequency bound of the audible sound beam with distance. The main focus is on the experimental setup, which permits the parametric sound generation with only one ultrasonic transducer and a waveguide. In addition, the new measurement setup enables to show an additional effect: The de-coherence of the primary ultrasound wave which may be caused by saturation of air. This is why the lower frequency bound decreases as well if we approach the ultrasonic transducer.

Novices' expectations and prior knowledge of software development: results of a study with high school students - Schulte, Carsten; Magenheim, Johannes (ICER)

Beiträge der Objektorientierung zu einem Kompetenzmodell des informatischen Modellierens - Brinda, Torsten; Schulte, Carsten (INFOS)

Erwartungen und Wahlverhalten von Schülerinnen und Schülern gegenüber dem Schulfach Informatik - Ergebnisse einer Umfrage - Schulte, Carsten; Magenheim, Johannes (INFOS)

Calibrated label-ranking - Brinker, K.; Hüllermeier, Eyke (In Proceedings of the NIPS-2005 Workshop on Learning to Rank, Whistler, BC, Canada)

On position error and label ranking through iterated choice - Hüllermeier, Eyke; Fürnkranz, J.; Beringer, J. (In Proceedings LWA/FGML-2005, German Workshop on Machine Learning, Saarbrücken, Germany)

Polariton propagation in shallow-confinement heterostructures: Microscopic theory and experiment showing the breakdown of the dead-layer concept - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Rückmann, H. I.; Gutowski, J.; Gust, A.; Alexe, G.; Hommel, D. (Physical Review B)

Coherent propagation of polaritons in semiconductor heterostructures: Nonlinear pulse transmission in theory and experiment - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Wischmeier, L.; Rückmann, I.; Voss, T.; Gutowski, J.; Gust, A.; Hommel, D. (Physical Review B)

A method for combining interacting pieces of evidence in case-based learning - Hüllermeier, Eyke; NN, Cho-k (in Proceedings IJCAI-05, 19th international Joint Conference on Artificial Intelligence, Edingburgh, Scotland)

Learning label preferences: Ranking error versus position error - Hüllermeier, Eyke; Fürnkranz, J. (In Proceedings IDA-2005, 6th International Symposium on Intelligent Data Analysis, Madrid)

Learning from ambiguously labeled examples - Hüllermeier, Eyke; Beringer, J. (In Proceedings IDA-2005, 6th International Symposium on Intelligent Data Analysis, Madrid)

Verbessern Tax-Master- und WP-Master-Studiengänge die Ausbildungsqualität von Steuerberatern und Wirtschaftsprüfern? - Bareis, Peter; Hachmeister, Dirk; Kahle, Holger; Kiesewetter, Dirk; König, Rolf; Maiterth, Ralf; Niemann, Rainer; Rückle, Dieter; Schneider, Dieter; Siegel, Theodor; Sureth-Sloane, Caren; Treisch, Corinna (Zeitschrift für Steuern und Recht)

Auswirkungen der Vermögensteuer als Mindeststeuer auf die Investitionstätigkeit und die Attraktivität Deutschlands im internationalen Standortwettbewerb - Maiterth, Ralf; Sureth-Sloane, Caren (Steuern und Bilanzen)

Wiedereinführung der Vermögensteuer als Mindeststeuer in Deutschland - Unlösbare Probleme bei der Bewertung von Grundbesitz und Unternehmen - Maiterth, Ralf; Sureth-Sloane, Caren (Steuern und Bilanzen)

Vermögensteuer, Verluste und Investitionsentscheidungen - Sureth-Sloane, Caren (ForschungsForum Paderborn)

Capital Gains Taxation under Different Tax Regimes - Sureth-Sloane, Caren; Langeleh, Dirk

Wealth Tax As Alternative Minimum Tax? - The Impact of a Wealth Tax on Business Structure and Strategy - Sureth-Sloane, Caren; Maiterth, Ralf

Investitionsbereitschaft und zeitliche Indifferenz bei Realinvestitionen unter Unsicherheit und Steuern - Sureth-Sloane, Caren; Voß, Armin

Vererben und Verschenken von US-amerikanischem, französischem und österreichischem unternehmerischen Vermögen - eine steuersystematische Analyse sowie daraus abgeleitete Gestaltungsansätze - Tanto, Olaf

Stability versus speed in a computable algebraic model - Ziegler, Martin (Theoretical Computer Science)

A notion of comarative probabilistic entroy based on the possibilistic specificity ordering - Dubois, D.; Hüllermeier, Eyke (in Proceedings ECSQARU-2005, 8th European Conference of Symbolic and Quantitative Approaches to Reasoning with Uncertainty, Barcelona, Spain)

Adaptive XML Access Control Based on Query Nesting, Modification and Simplification - Böttcher, Stefan; Steinmetz, Rita (Datenbanksysteme in Business, Technologie und Web, 11. Fachtagung des GI-Fachbereichs "Datenbanken und Informationssysteme" (DBIS))

Embedding XML Schema Constraints in Search-Based Intersection Tests for XPath Query Optimization - Böttcher, Stefan; Steinmetz, Rita (16th International Workshop on Database and Expert Systems Applications (DEXA'05))

Detecting Privacy Violations in Sensitive XML Databases - Böttcher, Stefan; Steinmetz, Rita (Secure Data Management, Second VLDB Workshop, SDM 2005)

A fuzzy-probablistic risk assessment system for natural disasters - Karimi, I.; Hüllermeier, Eyke (in Proceedings IFSA-2005, 11th World Congress of the International Fuzzy System Association, Beijing, China)

Improving the interpretability of data-driven evolving fuzzy systems - Lughofer, E.; Hüllermeier, Eyke; Klement, E. (in Proceedings EUSFLAT-2005 4th International Conference on the European Society for Fuzzy Logic and Technology, Barcelona, Spain)

Learning complexity-boundet rule-based classifiers by combining association analysis and genetic algorithms - Yi, Y.; Hüllermeier, Eyke (in Proceedings EUSFLAT-2005 4th International Conference on the European Society for Fuzzy Logic and Technology, Barcelona, Spain)

Fuzzy sets in machine learning and data mining: Status and prospects - Hüllermeier, Eyke (Fuzzy Sets and Systems)

Experience-based decision making: A satisficing decision tree approach - Hüllermeier, Eyke (IEEE Transactions on Systems, Man and Cybernetics-Part A: Systems and Humans)

Clustering of gene expression data using a local shape-based similarity measure - Balasubramaniyan, R.; Hüllermeier, Eyke; Weskamp, N.; Kämper, J. (Bioinformatics)

HGB: Basiswissen einschließlich Wechsel- und Scheckrecht Fälle und Lösungen auf interaktiver CD - Krimphove, Dieter

A Low Power Design for Embedded DRAMs with Online Consistency Checking - Oehler, Philipp; Hellebrand, Sybille
Keywords: WORKSHOP

Dynamic Routing: A Prerequisite for Reliable NoCs - Ali, Muhammad; Welzl, Michael; Hellebrand, Sybille
Keywords: WORKSHOP

Power Consumption Versus Error Correcting Capabilities in Embedded DRAMs - A Case Study - Oehler, Philipp; Hellebrand, Sybille
Keywords: WORKSHOP

The use of instant messaging in working relationship development: A case study - Trier, Matthias; Cho, Hee-Kyung; Kim, Eunhee (Journal of Computer-Mediated Communication)

IT-gestützte Modellierung und Analyse elektronischer Expertengemeinschaften (Modeling and Evaluation of Electronic Expert Communities) - Trier, Matthias (i-com)

Process-Oriented Production of Learning Units for Sustainable E-Learning Offerings - Müller, Claudia; Trier, Matthias; Herzog, Michael A. (E-Learning)

A Tool for IT-supported Visualization and Analysis of Virtual Communication Networks in Knowledge Communities - Trier, Matthias (Wirtschaftsinformatik 2005)

A Procedural Model for the Production of Reusable and Standard-Compliant E-Learning Offerings - Müller, Claudia; Trier, Matthias (Wirtschaftsinformatik 2005)

IT-Supported Visualization of Knowledge Community Structures - Trier, Matthias (Proceedings of the 38th Annual Hawaii International Conference on System Sciences)

Netzwerkorientiertes Wissensmanagement und seine Unterstützung durch Softwarewerkzeuge - Krallmann, Hermann; Trier, Matthias (Strategisches Wertschöpfungsmanagement in dynamischer Umwelt: Festschrift für Erich Zahn)

Adaptive scheduling for heterogeneous traffic flows in cellular wireless OFDM-FDMA systems - Valentin, Stefan; Gross, James; Karl, Holger; Wolisz, Adam (10th IFIP International Conference on Personal Wireless Communications/PWC'05, Comar, France, 2005)

Periodic real-time scheduling for FPGA computers - Danne, Klaus; Platzner, Marco (Proceedings of the Third International Workshop on Intelligent Solutions in Embedded Systems (WISES))

Memory-demanding Periodic Real-time Applications on FPGA Computers - Danne, Klaus; Platzner, Marco (Work-in-Progress Proceedings of the 17th Euromicro Conference on Real-time Systems (ECRTS))

A heuristic approach to schedule periodic real-time tasks on reconfigurable hardware - Danne, Klaus; Platzner, Marco (Proceedings of the 15th International Conference on Field Programmable Logic and Applications (FPL))

Quasiparticle bands and optical spectra of highly ionic crystals: AlN and NaCl - Bechstedt, F.; Seino, K.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Attracted by Long-Range Electron Correlation: Adenine on Graphite - Ortmann, F.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Calculation of reflectance anisotropy for semiconductor surface exploration - Schmidt, Wolf Gero (physica status solidi (b))

Quasiparticle and excitonic effects in the optical spectra of diamond, SiC, Si, GaP, GaAs, InP, and AlN - Hahn, P. H.; Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (physica status solidi (b))

VUV-ellipsometry on GaN: Probing conduction band properties by core level excitations - Esser, N.; Rakel, M.; Cobet, C.; Schmidt, Wolf Gero; Braun, W.; Cardona, M. (physica status solidi (b))

Initial Stage of Si(001) Surface Oxidation from First-Principles Calculations - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (The Journal of Physical Chemistry B)

Understanding the optical anisotropy of oxidized Si(001) surfaces - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Coulombic Amino Group-Metal Bonding: Adsorption of Adenine on Cu(110) - Preuss, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Conformation-selective adsorption of 2,3-butanediol on Si(001) - Seino, K.; Schmidt, Wolf Gero (Surface Science)

Second-harmonic polarizability including electron-hole attraction from band-structure theory - Leitsmann, R.; Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Optical response ofπ-conjugated molecular monolayer adsorbed on the semiconductor Si(001) surface: A first-principles study - Hermann, A.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Phenanthrenequinone Adsorbed on Si(001): Geometries, Electronic Properties, and Optical Response - Hermann, Andreas; Schmidt, Wolf Gero; Bechstedt, Friedhelm (The Journal of Physical Chemistry B)

Optical Absorption of Water: Coulomb Effects versus Hydrogen Bonding - Hahn, P. H.; Schmidt, Wolf Gero; Seino, K.; Preuss, M.; Bechstedt, F.; Bernholc, J. (Physical Review Letters)

A study of impact of inband signalling and realistic channel knowledge for an example dynamic OFDM-FDMA system - Gross, James; Valentin, Stefan; Karl, Holger; Wolisz, Adam (European Transactions on Telecommunications)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Von der Ontologie zur Begriffsanalytik. Kants Beitrag zu den aktuellen Diskussionen über Metaphysik und Ontologie - Ficara, Elena (Philosophie von Immanuel Kant und die Gegenwart)

Vorwort - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)
Rezensionen: History and Philosophy of Logic 27 (2006), 198–200 (Dirk Schlimm); Bulletin of Symbolic Logic 12 (2006), 137–139 (R. Vilkko); NTM 15 (2007), 67–68 (K. Radbruch); Philosophiques 35 (2008), 612–613 (Y. Gauthier).

Einleitung: Oskar Becker und die Philosophie der Mathematik - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)

Rationalismus zwischen Vision und Wirklichkeit. Descartes, Leibniz und die Grenzen des Machbaren - Peckhaus, Volker (ForschungsForum Paderborn)

Comparison of Performance and Realization Effort of a Very Sparse Matrix Converter to a Voltage DC Link PWM Inverter with Active Front End - Round, Simon; Schafmeister, Frank; Pereira, Eduardo; Serpa, Leonardo; Kolar, Johann (Proc. 5th IEEJ International Power Electronics Conference (IPEC))

Analytical Calculation of the Conduction and Switching Losses of the Conventional Matrix Converter and the (Very) Sparse Matrix Converter - Schafmeister, Frank; Rytz, Christoph; Kolar, Johann (Proc. 20th IEEE Applied Power Electronics Conference (APEC))

Enhanced Control Scheme for Three-Phase, Three-Level Rectifiers at Partial Load - Ide, Peter; Schafmeister, Frank; Fröhleke, Norbert; Grotstollen, Horst (IEEE Transactions on Industrial Electronics)

Design and implementation of a hybrid energy supply system for railway vehicles - Li, R.; Pottharst, A.; Fröhleke, N.; Böcker, Joachim; Witting, K.; Dellnitz, M.; Znamenshchykov, O.; Feldmann, R. (Twentieth Annual IEEE Applied Power Electronics Conference and Exposition, 2005. APEC 2005.)

Design of Long-Stator Linear Motor Drives for RailCab Test Track - Grotstollen, H. (Journal of Power Electronics (JPE))

Convoy Operation of Linear Motor Driven Railway Vehicles, Kobe - Awaji, Japan - Henke, C.; Vöcking, H.; Böcker, Joachim; Fröhleke, N.; Trächtler, A. (LDIA 2005, The Fifth International Symposium on Linear Drives for Industry Applications)

Simulation of Power Electronic Circuits - Grotstollen, H.; Böcker, Joachim; Fröhleke, N. (ICSC 2005, Peking, China)

ZVZCS Isolated Converter for Renewable Energy System with Extra Wide Voltage Range - Li, R.; Fröhleke, N.; Böcker, Joachim; Ide, P. (International PCIM Conference 2005, Nürnberg, Deutschland)

Distributed Control Structure of the NBP Test Track with Linear Motor Driven Vehicles - Pottharst, A.; Grotstollen, H. (International Embedded Systems Symposium, Manaus, Brasil)

Impliziert Widerspruchsfreiheit Existenz? Oskar Beckers Kritik am formalistischen Existenzbegriff - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)

Becker und Zermelo - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)

19th Century Logic: Between Philosophy and Mathematics (Wiederabdruck) - Peckhaus, Volker (Mathematics and the Historian’s Craft. The Kenneth O. May Lectures)

Algèbre de la logique, théorie de la quantification et carré des oppositions - Peckhaus, Volker (La quantification dans la logique moderne)

Calculus Ratiocinator vs. Characteristica Universalis? The Two Traditions in Logic, Revisted (Wiederabdruck) - Peckhaus, Volker (Gottlob Frege. Critical Assessments of Leading Philosophers, Bd. 1: Frege’s Philosophy in Context)
Rezension: Zbl. Math. 1100.03006 (I. Grattan-Guinness)

Wahlfolge - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Wahrheitsfunktion; Wahrheitstafel - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Widerspruchsfreiheit - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Wohlordnungssatz - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Bochenski, Joseph Maria - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 1: A–B)

Bachmann, Karl Friedrich - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 1: A–B)

Zirkel - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Aegidius Romanus - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 1: A–B)